Parametric study on thermal enhancement and flow characteristics in a heat exchanger tube installed with protruded baffle bundles - Eiamsa-ard, S.; Ruengpayungsak, K.; Thianpong, C.; Pimsarn, M.; Chuwattanakul, V. (My University, 2019)
Influence of protruded baffle turbulators (P-BTs) on turbulent convective heat transfer rate and thermal performance behavior in round tubes was experimentally studied. The following geometrical parameters of P-BTs were considered (i) spacing ratio (SR = s/Dob = 1.0–3.0), (ii) diameter ratio (DR = d/Dob = 0.2–0.4), (iii) baffle orientation angle (θ = 0° (without rotation), 60°, 120° and 180°), and (iv) Reynolds number (Re = 6000 to 20,000). Air was used as working fluid at Prandtl number of Pr = 0.71. The plain tube data was examined for comparison with tube installed with protruded baffle turbulators (P-BTs). The experimental results obvious that increasing baffle orientation angle (θ), increasing diameter ratio (DR) and decreasing spacing ratio (SR) lead to the significant increases in heat transfer (Nu) and pressure loss (f). It can be also reveal that thermal performance (η) at a given Re considerably increases with the increasing spacing ratio (SR) and the reduction of diameter ratio (DR) and baffle orientation angle. The P-BTs with larger baffle orientation angle, induce stronger vortex ring and longitudinal vortex behind the baffles, give higher the thermal performance. Furthermore, all of empirical correlations (Nu, f and η) were derived as a function of Re and the protruded baffle turbulator (P-BT) geometry parameters including spacing ratio (SR), and protrusion-diameter ratio (DR).
Keywords: Heat transfer enhancement; Protruded baffle; Turbulator; Turbulent promoter